Proyecto de inversión para la creación de una empresa para la organización de eventos sociales en el cantón Salcedo, provincia de Cotopaxi, Ecuador. - Soria Albán, Zaira Estefanía (2025)
In today’s world, where social life and celebrations are a fundamental part of individuals’ social interactions, social event planning companies play a crucial role. Therefore, this investment project aims to solve social issues related to the organization and management of events. This type of establishment aligns with the needs of the population seeking to manage and organize their events. To support this investment project, it is based on theoretical aspects supported by bibliographic references from authors such as Andreina, Flores, Prieto, and Zurita, who discuss the components of an investment plan. The market segment interested in organizing and managing their events has grown in recent years. This conclusion was drawn from the research, which implemented a qualitative and quantitative methodology through field and documentary research. Additionally, we applied survey tools to users and established event planning companies in the Canton, which allowed us to determine our market segment and the demand the company will have upon entering the area. As a result of the research and as a contribution to the proposal, promotional sales strategies and communication channels were identified. These strategies ensure the project’s viability and feasibility, allowing our clients to enjoy the best experiences and unforgettable moments.